Integrated Knowledge Management Tools for Sharing Knowledge in Implementing Building Information Modelling (BIM): The Case of Malaysian Construction Organisations - Musa, Suria; Marshall-Ponting, Amanda; Shahron, Syairah Aimi; Abdullah, Rohani; Abd Aziz, Nor Erlissa (2022)
Building Information Modelling is an innovative technology coupled with the process and human interactions. BIM has been used by the Architecture, Engineering, and Construction (AEC) industry in developed and developing countries, including Malaysia. Implementing BIM in construction organisations involves knowledge sharing between employees in the organisations, as well as project team players from other organisations due to the nature of project-based organisations and the multidisciplinary players. This paper aims to explore and identify the KM tools used for sharing knowledge in implementing BIM in Malaysian Construction Industry. This paper begins with a literature review and then reports on the findings of case studies of selected Malaysian construction organisations. The review highlights several KM tools or approaches used to support KM processes and sub-processes. The result from the analysis showed that KM tools used to facilitate KS in implementing BIM was a balance between the application of KM technologies and KM techniques, which indicates the equal importance of both tools in supporting KS in implementing BIM.